2010
DOI: 10.1055/s-0030-1258359
|View full text |Cite
|
Sign up to set email alerts
|

Direct Organocatalytic α-Sulfenylation of Aldehydes and Ketones with Tetramethylthiuram Disulfide

Abstract: The direct pyrrolidine-catalyzed a-sulfenylation of aldehydes and ketones with the commercially available, very cheap chemical tetramethylthiuram disulfide (thiram) is described. The dithiocarbamoyl derivatives are obtained in good to excellent yields (47-98%). In the case of a-substituted aldehydes the protocol allows the generation of quaternary stereocenters. The sensibility of the a-sulfenylated carbonyl compounds for racemization has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 4 publications
1
23
0
Order By: Relevance
“…To our knowledge, there are just few examples of direct catalytic a-sulfanylation of unmodied carbonyl compounds which are based on the use of N-(phenylthio)phthalimide 6b or sulfonyl chloride derivatives 6 but excluding the interesting results obtained by Enders and co-workers using tetramethylthiuram disulde, 11 no examples of organocatalyzed reactions involving diaryldisuldes as reagents have been reported to date. In this paper we now wish to report the development of a new proline-catalyzed ketosulde synthesis from aryldi-suldes and ketones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are just few examples of direct catalytic a-sulfanylation of unmodied carbonyl compounds which are based on the use of N-(phenylthio)phthalimide 6b or sulfonyl chloride derivatives 6 but excluding the interesting results obtained by Enders and co-workers using tetramethylthiuram disulde, 11 no examples of organocatalyzed reactions involving diaryldisuldes as reagents have been reported to date. In this paper we now wish to report the development of a new proline-catalyzed ketosulde synthesis from aryldi-suldes and ketones.…”
Section: Introductionmentioning
confidence: 99%
“…As expectable, analogous results in terms of yields and reaction times were achieved with those observed for D,L-proline but unluckily, HPLC analysis of the isolated cyclobutanone 2a showed the formation of a racemate. 11 Reactions employing other chiral not racemic pyrrolidine-catalysts (see ESI †), were also inefficient in terms of asymmetric induction. We believe that this result can be rationalized by taking in consideration, the reduced formation of a stable hydrogen-bonding interaction between the disulde and the transient enamine-adduct due to the operation high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, different bases were screened and K 2 CO 3 was chosen as the best one (entries [6][7][8]. As for benzyl bromides, substituents ranging from weak electron-withdrawing groups, such as Br and methyl ester, to strong electronwithdrawing groups, such as NO 2 , along with electron-donating methoxyl groups, all furnished the desired benzyl diethyldithiocarbamates in good yields (entries [15][16][17][18][19][20]. The optimal reaction conditions were summarized in entry 9 and the subsequent control experiments (entries [11][12] revealed that 100°C was the most suitable temperature for benzyl bromide.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11] Some methods for their synthesis involve the reaction of benzyl alcohols and dithiocarbamates. [15,16] However, these methods require using large amounts of organic solvents, toxic and foul smelling reagents, or organometallic reagents sensitivity to air and moisture, which limit their application in pharmaceutical synthesis. [15,16] However, these methods require using large amounts of organic solvents, toxic and foul smelling reagents, or organometallic reagents sensitivity to air and moisture, which limit their application in pharmaceutical synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…1 As a result, thiuram reagents have achieved multifield applications as vulcanization promoters, animal repellents, and antifungal agents. 2 Among these, sodium dialkyl dithiocarbamates are widely used in industrial compounds for downstream usage of medicines, 3 pesticides, 4 and vulcanization accelerators. 5 They can also be used as easily available sulfur reagents in synthetic chemistry.…”
mentioning
confidence: 99%